COVID-19 Vaccination Did Not Change the Personal Protective Behaviors of Healthcare Workers in China - Zhang, Nan; Lei, Hao; Li, Li; Jin, Tianyi; Liu, Xiyue; Miao, Doudou; Su, Boni; Bu, Zhongming; Fan, Lin; Xue, Peng; Xie, Jingchao; Li, Yuguo (Frontiers in Public Health, 2021)
Personal protective behaviors of healthcare workers (HCWs) and dynamic changes in them are known to play a major role in the hospital transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this study, 1,499 HCWs in Chinese hospitals completed an online survey about their knowledge on SARS-CoV-2 transmission and their personal protective behaviors before and after coronavirus disease 2019 (COVID-19) vaccination. Of all the respondents, 89% were vaccinated at the time of the survey and 96% believed that the vaccine was effective or highly effective. Further, 88% of the vaccinated HCWs expressed that they would get revaccinated if the vaccination failed. Compared with HCWs with a lower education level, those with a higher education level had less fear of being infected with SARS-CoV-2 and reported a lower negative impact of the pandemic on how they treated patients. Physicians and nurses were willing to believe that short-range airborne and long-range fomite are possible transmission routes. HCWs with a higher education level had a better knowledge of COVID-19 but worse personal protective behaviors. The fact that HCWs with a longer work experience had worse personal protective behaviors showed that HCWs gradually relax their personal protective behaviors over time. Moreover, vaccination reduced the negative effects of the COVID-19 pandemic on how the HCWs treated patients. Importantly, the survey revealed that after vaccination, HCWs in China did not relax their personal protective behaviors, and it may bring a low potential risk for following waves of variant virus (e.g., delta).